Cracking Behavior and High-Temperature Thermoplastic Analysis of 09CrCuSb Steel Billets - Zhixian Peng; Tao Mei; Jian Zheng; Yuan Yuan; Liwang Wang (Metals, 2023)
This paper characterizes the surface crack morphology and elements of 09CrCuSb steel continuous casting slabs and studies the high-temperature thermo-plasticity of continuous casting slabs using a Gleeble 3500 thermal simulator. Combining the macro/micro fracture morphology and microstructure characteristics, the formation rules of slab cracks are discussed. The research results show that the increase in Ae3 temperature caused by changes in alloy elements results in the precipitation of a thin, film-like coexisting ferrite along the grain boundaries at a certain temperature, as well as the element segregation behavior of low-melting-point alloy elements at the original austenite grain boundaries, which are the main factors inducing cracks in 09CrCuSb steel continuous casting billets. The plasticity of 09CrCuSb steel at high temperatures is poor at 800~900 °C. In continuous casting process control, it is necessary to try to avoid long-term stay of the billet at this temperature range.